Sharia Compliance and Legal Certainty in the Governance of Islamic Banking In Indonesia - Cintia Nurul Lita Br Silalahi; Muhammad Albahi; Raja Sakti Putra Harahap (Jurnal Ekonomi Bisnis dan Manajemen, 2026)
The development of the Islamic banking industry in Indonesia demands a strong integration between normative aspects and operational legality. This study aims to analyze the implementation of sharia compliance in Islamic banking governance in Indonesia and examine its contribution to achieving legal certainty. Using a qualitative method with a juridical-normative approach, this research examines secondary data through library research and a statutory approach. The results indicate that sharia compliance is a fundamental principle that serves as a key indicator of the credibility and integrity of Islamic financial institutions. Sharia governance acts as a mediating variable that connects sharia compliance to legal certainty through mechanisms of transparency, accountability, and the strategic role of the Sharia Supervisory Board (DPS). Although supported by Law No. 21 of 2008 and Law No. 4 of 2023 (UU P2SK), legal certainty still faces challenges such as the dualism of the legal system and differing interpretations of sharia principles. The study concludes that strengthening adaptive regulations, improving human resource quality, and harmonizing Islamic law with national positive law are essential to creating a sustainable and competitive Islamic banking ecosystem.